CHARACTERISTICS AND EXPERIENCES OF BIRDWATCHER IN INDONESIA - Insan Kurnia; Harnios Arief; Ani Mardiastuti; Rachmad Hermawan (Department of Forest Resources Conservation and Ecotourism - IPB University, 2023)
Birdwatching is one of nature recreations focusing on enjoying the wild birds. This activity is a hobby that continuously develops and has high economical value, besides beneficial related to conservation. A study of birdwatching in Indonesia is only focused on a bird potential supply concept in various locations without any demand study. A demand study is expected to become the basic of birdwatching management following the birdwatcher desire. This study aimed to analyze the birdwatcher characteristics in Indonesia on demographical, experience, motivation, and preference aspects. The study was performed on February to April, 2020 using online questionnaire distributed to Indonesian birdwatchers. The respondents who completely filled or nearly filled the questionnaire were 1257 birdwatchers. The respondent demographic is dominated by male, adolescent and early adult, living in the city, high educational background, and conservation organization member. The birdwatching experience is dominated by less than 3 hours activity. The protected area becomes the most-visited location by birdwatchers followed by the urban landscape. Bird identification is mostly carried out through visuals rather than through sounds. The most commonly used equipment is the bird fieldguide and binoculars.